An Assistance Teachers of Development Google Slide-Based Learning Media at School - Adi Wijaya; Ehwanudin; Rifki Nur Salis (Yayasan Payungi Smart Madani, 2022)
This community service is motivated by the lack of skills, insight and competence of teachers in the use of technology as a learning medium. The learning activities of students only listen to explanations from the teacher and take notes on learning materials. So that learning seems less interesting, monotonous, and only teacher-cantered. Therefore, the purpose of this community service is to develop Google Slide for school or madrasah teachers in Lampung Province, apply and utilize Google Slides, and seek to improve the quality of teachers in using technology as a learning media tool. This study uses the lecture method and the method of practice (drill practice) the manufacture and development of learning media based on Google Slides. The drill practice is an activity of doing the same thing, and is done repeatedly and earnestly with the aim of perfecting a skill so that it becomes permanent. The results of this community service are in the form of Google Slide that can be used as a learning media tool to convey information and learning materials are more interesting. In addition, this service activity also received a positive response, as evidenced by the enthusiasm of the teachers in following through to completion so that they could develop Google Slides learning media.